Evolução da pressão arterial e desfechos cardiovasculares de hipertensos em centro de referência - Guimarães Filho, Gilberto Campos (2014)
High blood pressure (HBP) is a chronic disease with high prevalence and the main risk factors for the development of cardiovascular diseases. It is therefore a major public health problem and a major challenge to health professionals. Its close relationship with other risk factors and the knowledge that their treatment alters the natural history of diseases of the cardiovascular apparatus, makes the effective control of blood pressure (BP) reduce, significantly, cardiovascular outcomes such as Accident cerebrovascular (stroke), acute myocardial infarction (MI), chronic kidney disease (CKD) and Death. Based on this knowledge of health programs has been developed for the prevention and control of hypertension. Objective: To evaluate the level of BP control, risk factors and cardiovascular outcomes in hypertensive patients registered within the Reference Center for Hypertension and Diabetes (CRHD) of a medium-sized city in the Midwest region for the period 2003-2012 Methodology.: it is about quasi-experimental study with a quantitative approach, performed in specialized service with hypertensive, of both genders, aged over 18 years, registered in HIPERDIA system been followed for at least 6 months. A representative sample of patients the service was investigated by aleatory drawing. Collected data regarding the unit admission and follow-up through home visits, and analyzed: demographic variables, blood pressure, body mass index (BMI), BP measurements, risk factors and cardiovascular outcomes. Data collection was for the period 2003 to 2012, the Chi-square or Fisher tests, Kolmogorov-Student t test, Wilcoxon test were used.; significance level of 0.05, confidence interval of 95%. Results: There was a predominance of females. Over time, a significant increase in the prevalence of overweight, physical inactivity, alcohol consumption, diabetes mellitus and dyslipidemia. Chronic complications have risen 12.4% strokes being observed, followed by MI (10.5%), CKD (10.5%), CABG (6.4%) and finally Death (5.5%). There was a significant improvement (p = 0.001) rates of BP control during follow-up period from 29.6% at admission to 39.6% at follow-up. Conclusion: Despite considerable improvements in the rate of blood pressure control during follow-up of the subjects, these numbers were not encouraging. There were also increases in the presence of risk factors.